2014
DOI: 10.1007/s13592-014-0335-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of the honeybee (Apis mellifera) population of Rodrigues Island, based on microsatellite and mitochondrial DNA

Abstract: -Apis mellifera is present in Rodrigues, an island in the South-West Indian Ocean. The history of the established honeybee population is poorly known, and its biodiversity has never been studied. In this study, maternal origins of A. mellifera in Rodrigues have been assessed with the DraI test and sequencing of the mitochondrial COI-COII region. Nuclear genetic diversity was investigated with 18 microsatellite markers. A total of 524 colonies were sampled from 16 beekeepers in 20 sites. The Rodrigues populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 46 publications
(49 reference statements)
5
17
0
Order By: Relevance
“…C1_a have been previously observed in Rodrigues [44] and was also detected in 20 colonies from Mauritius. C1_a haplotype is considered as characteristic of A. m. ligustica populations and was already found in Italy [6].…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…C1_a have been previously observed in Rodrigues [44] and was also detected in 20 colonies from Mauritius. C1_a haplotype is considered as characteristic of A. m. ligustica populations and was already found in Italy [6].…”
Section: Resultssupporting
confidence: 68%
“…The most extreme case was the honey bee population from Rodrigues which was previously described as exclusively belonging to the C lineage using COI-COII [44]. This assertion is now confirmed by the ND2 marker.…”
Section: Discussionmentioning
confidence: 62%
“…Despite mtDNA similarities, using microsatellite markers, honey bee populations between the Seychelles Archipelago and Madagascar (separated by 1,100 km of ocean) were found to be genetically differentiated [ 38 ]. In the Mascarenes, proportions of mtDNA haplotypes from the European lineage drastically varied from an island to another [ 37 ] reaching an exclusive level in the eastern Rodrigues population [ 39 ]. These findings confirmed that multiples introductions occurred in the Mascarenes but their effect on La Réunion and Mauritius populations have never been characterized using nuclear markers.…”
Section: Introductionmentioning
confidence: 99%
“…Since multiples lineages coexist in these islands, processes shaping the genetic diversity are hard to disentangle without a large and diverse dataset, capable of discerning between African and European populations. For that reason, we implemented additional sampling from continental native populations and previous datasets from Madagascar [ 40 ], Seychelles [ 38 ], and Rodrigues [ 39 ], to assess the relationship among insular and continental populations. Using the most comprehensive genetic dataset of A .…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we present information resulting from microsatellite genotyping to evaluate the detailed genetic diversity and population structure of two subspecies (A.m. scutellata and A.m. capensis) and their hybrids from 29 regions in the RSA. Microsatellite loci have been widely used to characterize the structure of honey bee populations across different geographical regions since they have a high degree of sensitivity and provide a reasonable level of polymorphism (Franck et al, 2001;Loucif-Ayad et al, 2015;Techer et al, 2015).…”
Section: Discussionmentioning
confidence: 99%